PEMODERASIAN PERPUTARAN ASET TETAP DALAM MENGANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, DAN ARUS KAS BEBAS TERHADAP MANAJEMEN LABA EFISIEN ATAU LABA OPORTUNISTIK - Deden Iwan Kusuma; Citra Dindha Firmana Puspa Agny (LPPM STIE YKPN Yogyakarta, 2022)
This study aims to determine the earnings management conducted by the company whether it is efficient earnings management or opportunistic earnings management, because earnings management is common and often done by companies and what factors influence the earnings management behavior of the company. To find out the type of earnings management carried out by the company, it will be measured using Accrual Discretion (DA), while measuring the factors that influence earnings management by the company uses Profitability (Return On Assets (ROA)), Liquidity (Current Ratio (CR)), and Free Cash Flow (FCF). To strengthen researchers' confidence in earnings management carried out by the company, one factor that supports other factors is Perputaran aset tetap (FATO). This research takes data from service companies that have been listed on the Indonesia Stock Exchange during the period 2019-2021 in the Property, Real Estate, and Building Construction sectors. The results of this study indicate that earnings management conducted by companies tends to be opportunistic, profitability and liquidity influence opportunistic earnings management, while free cash flow has an effect on efficient earnings management. Fixed asset turnover does not moderate the effect of the three factors on earnings management.